2015
DOI: 10.1002/ima.22132
|View full text |Cite
|
Sign up to set email alerts
|

Feed‐forward neural network optimized by hybridization of PSO and ABC for abnormal brain detection

Abstract: Automated and accurate classification of MR brain images is of crucially importance for medical analysis and interpretation. We proposed a novel automatic classification system based on particle swarm optimization (PSO) and artificial bee colony (ABC), with the aim of distinguishing abnormal brains from normal brains in MRI scanning. The proposed method used stationary wavelet transform (SWT) to extract features from MR brain images. SWT is translation-invariant and performed well even the image suffered from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 184 publications
(56 citation statements)
references
References 39 publications
(62 reference statements)
0
53
0
Order By: Relevance
“…Wang [9] demonstrated that HPA's performance was better than other hybridizations, and SLFN has achieved good results in terms of classification. Therefore, Lu [10] proposed a novel "HPA + SLFN" method.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Wang [9] demonstrated that HPA's performance was better than other hybridizations, and SLFN has achieved good results in terms of classification. Therefore, Lu [10] proposed a novel "HPA + SLFN" method.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Yang et al [21] selected wavelet-energy as the features, and introduced biogeography-based optimization (BBO) to train the SVM. Wang et al [22] suggested to use stationary wavelet transform (SWT) to replace DWT, and then they proposed a hybridization of PSO and ABC (HPA) algorithm to train the classifier. Zhang et al [23] suggested to use a 3D eigenbrain method to detect subjects and brain regions related to AD.…”
Section: Y Zhang Et Al / Abnormal Brain Detection By We and Qpsomentioning
confidence: 99%
“…Good classification percentage of 96% was achieved using the RBF when Daubechies (db4) wavelet based feature extraction was used. Wang et al [26] suggested to use stationary wavelet transform (SWT) to replace DWT, and then they proposed a hybridization of PSO and ABC (HPA) algorithm to train the classifier. Zhang et al [27] proposed a novel classification system that implemented 3D discrete wavelet transform (3D-DWT) to extract wavelet coefficients the volumetric image.…”
Section: Existing Pathological Brain Detection Systemsmentioning
confidence: 99%
“…We compared the proposed HBP with BP [37], MBP [38], GA [39], SA [40], 2.4.1 [41], BBO [42], PSO [43], and BPSO [50] III. We compared the proposed HBP-FNN with fourteen state-of-the-art classification methods as DWT + PCA + FP-ANN [7], DWT + PCA + KNN [7], DWT + PCA + SCABC-FNN [8], DWT + PCA + SVM + HPOL [11], DWT + PCA + SVM + IPOL [11], DWT + PCA + SVM + GRB [11], WE + SWP + PNN [12], RT + PCA + LS-SVM [14], PCNN + DWT + PCA + BPNN [17], DWPT + SE + GEPSVM [18], DWPT + TE + GEPSVM [18], WE + NBC [19], WEnergy + SVM [22], and SWT + PCA + HPA-FNN [26]. IV.…”
Section: Experiments Designmentioning
confidence: 99%